2017
DOI: 10.1007/s11665-017-3016-9
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characterization of SiC and B4C Manufactured by Plasma Pressure Compaction

Abstract: The objective of the present study was to assess the tribological properties and the wear behavior of silicon carbide and boron carbide ceramics, produced by the plasma pressure compaction sintering process. Reciprocating sliding tests were executed to evaluate the tribological behavior of silicon carbide and boron carbide. Samples of each material with distinct values of surface roughness Ra were tested. Wear mass loss, coefficients of friction and wear mechanism of the boron carbide and silicon carbide were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Rubino et al reported that the B 4 C ceramics with different surface roughness (R a = 0.9, 1.3, 1.9¯m) exhibited different friction coefficients during runin period. 11) The B 4 C ceramics with higher surface roughness (R a ) showed a slightly lower friction coefficient.…”
Section: Surface Roughness Parameters and Surface Morphologiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Rubino et al reported that the B 4 C ceramics with different surface roughness (R a = 0.9, 1.3, 1.9¯m) exhibited different friction coefficients during runin period. 11) The B 4 C ceramics with higher surface roughness (R a ) showed a slightly lower friction coefficient.…”
Section: Surface Roughness Parameters and Surface Morphologiesmentioning
confidence: 94%
“…Rubino et al also stated that for SiC ceramics, the SiC ceramics with initial smoother surface (R a = 0.5¯m) had a higher friction coefficient than that of the SiC ceramics with initial rougher surface (R a = 2.2¯m) during run-in period. 11) The friction coefficient is decided by the asperities and protrusion between the two mating surfaces at the beginning of the test. The rougher surface means a lower number of contact points, which needs a smaller force to break these conjunctions.…”
Section: Jcs-japanmentioning
confidence: 99%
See 3 more Smart Citations